RELATIONS WITH THE USE OF SOAP CLEANING WOMANHOOD WHITISH IN WOMEN OF CHILDBEARING AGE EVENTS IN THE KADIREJO KARANGANOM KLATEN - Ayou Auliya; R. Taufiq Nur Muftiyanto; Putri Kusumawati Priyono (STIKES DUTAGAMA KLATEN, 2017)
Background: Central Java in 2009 the number of women in Central Java, which is 2.9 million, 45% of them experienced vaginal discharge (Semarang Health Office, 2010). While the incidence of vaginal discharge in Klaten district reached 25%. The use of excessive feminine hygiene soaps can cause vaginal discharge, because of feminine hygiene soaps contain chemicals that are very hard, which can irritate the soft areas such as the vagina and can shut off the natural ecological balance on the genital area. Aim: To determine the use of soap and feminine hygiene correlation with the incidence of vaginal discharge in women of childbearing age in the village Kadirejo Karanganom Klaten district. Research Methods: The research design was analytical survey, which surveys or research. The population in this study were all women of childbearing age in the village Kadirejo Karanganom Klaten district. A population of 728 respondents. Instrument research questionnaire and data analysis using chi square.Research Result: Respondents who experience vaginal discharge as many as 27 people (51.9%). Respondents who use soap femininity as many as 26 people (50%). No use of soap and feminine relationship with the incidence of vaginal discharge in women of childbearing age. Conclusion: No use of soap and feminine relationship with the incidence of vaginal discharge in women of childbearing age.